دور قبیلة ربیعة في تاریخ المشرق في العصر الراشدي والأموي (Journal of the College of Education for Women, 2019)
Rabi’a played an important part in the conquer of the east. This tribe hadasked to conquer the fareway provinces, in spite of these difficulties, Rabi’adid that and settled in.This tribe was among the opposition of the Umayyad caliphate in the east,because this tribe thinks that the caliphate was with the Mudhariyat andQaisiat tribes who were their enemies.In spite of that, they were very limited cases in which Rabi’a was theadherence of the caliphate against her enemies like Al-Harith b. Surieg , andwere against Qutaiba b. Muslim al- Bahily.Rabi’a assisted Amr b. Muslim movement against the Umayyad governorQutaibe, because the later wanted to sent her faraway from Mawara al- Nahar.Rabi’a dislikes Nasir b. sayiar who was well known in enmity to Rabi’a andher alliance because of the alliance between Rabi’a and the Yemen they managed toget many victories. The sources mention that some of Rabi’a preferred theAbbasids movement in defiance of Umayyad.